EFEKTIFITAS EKSTRAK BAWANG PUTIH (Allium sativum L) DALAM MENGHAMBAT PERKEMBANGBIAKAN BAKTERI Escherichia coli PADA BAKSO SAPI - Mey Anggraeni Tamal; Dhani Aryanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
The purpose of this study was to determine the best concentration of garlic extract in inhibiting e coli bacteria proliferation and the best storage time from beef meatballs has been soaked in garlic extract. Deskriptive statistical methods were used by soaking beef meatballs samples in garlic extract with different concentration, namely 0, 20, 40, and 60% for 15 minutes. Then samples are stored at room temperature ranging from 22-31 degrees celcius for 1, 3, and 5 days. The variable observed were e coli bacterial concentration using Total Plate Count (TPC) calculation. The results showed that the best concentration of garlic extract in inhibiting e coli bacterial proliferation was 40% and the best storage time was 1 day but can also be stored for 5 days